Dataset on child vaccination in Brazil from 1996 to 2021 - Boccolini, Patricia de Moraes Mello (2023)
Oswaldo Cruz Foundation. Institute of Scientific and Technological Communication and Information in Health. Rio de Janeiro, RJ, Brazil / Petropolis Medical School. Center for Information, Public Policies and Social Inclusion. Petrópolis, RJ, Brazil.